2022
DOI: 10.1177/09576509211059935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inflow conditions on transonic turbine airfoil limit loading

Abstract: To better understand airfoil limit loading and the effect inflow conditions have on local efficiency, a computational fluid dynamic investigation was performed for four different transonic turbine airfoils under sub-critical, critical, and supercritical conditions. A computational baseline was established using data previously collected at the Pratt and Whitney Canada High-Speed Wind Tunnel at Carleton University near design conditions using the Reynolds-Averaged Naiver-Stokes shear stress transport k − ω turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Expanding on this work, Owen investigated the effects of off-design inflow conditions for four different transonic turbine airfoils over a similar range of pressure ratios by varying inflow boundary conditions: incidence from ±20°, turbulence intensity from 5 to 20% and turbulent length scale from 1 to 100% of the airfoil pitch. 6 Similar to previous experimental work, it was shown that the limit loading pressure ratio and the mass-flow averaged outlet flow angle were strongly correlated with the airfoil outlet metal angle. The influence of inflow conditions on the exit flow profile was found to be minimal with the exception of the mass-flow averaged total pressure loss coefficient.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Expanding on this work, Owen investigated the effects of off-design inflow conditions for four different transonic turbine airfoils over a similar range of pressure ratios by varying inflow boundary conditions: incidence from ±20°, turbulence intensity from 5 to 20% and turbulent length scale from 1 to 100% of the airfoil pitch. 6 Similar to previous experimental work, it was shown that the limit loading pressure ratio and the mass-flow averaged outlet flow angle were strongly correlated with the airfoil outlet metal angle. The influence of inflow conditions on the exit flow profile was found to be minimal with the exception of the mass-flow averaged total pressure loss coefficient.…”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, the large change in outlet flow angle can drastically decrease the efficiency of downstream blade rows through a change in incidence angle. A quick interpolation of results from Owen, 6 shows that for a change of incidence by less than 2°, such as the change from critical to limit loading, total pressure loss is expected to rise by roughly 1%. However, as the incidence angle is significantly changed (>9°), such as is the case for supercritical loading, the estimated loss increase is roughly 25%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation